2015
DOI: 10.11113/jt.v77.6040
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Adoption in Higher Education: a Case Study of Universiti Utara Malaysia

Abstract: The use of social media within higher learning institute has resulted positive impacts on students engagement in teaching and learning activities. Current studies have acknowledged the importance of social media as one of the facilitating tools that promotes active participations among students. Although higher learning institution is introduce to new innovation, but when it comes to adopting they are always considered as late adopter. Thus, these studies examine the level of social media usage among lecturers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…From a faculty member adoption point of view, researchers are interested in examining: 1) how faculty members use the social media application, 2) what are the barriers/obstacles and challenges faced by faculty members when using the social media application for teaching and 3) factors that promote use of social media applications among faculty members [18][33][40] [41]. Previous studies indicated that faculty adoption of social media is still at the early majority adoption level [4]. At this level of adoption, faculty members agreed on the importance and success of adopting the social media application but, they are still cautious on giving their full commitment and efforts in using this application for teaching purposes.…”
Section: Social Media Use For Teaching and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…From a faculty member adoption point of view, researchers are interested in examining: 1) how faculty members use the social media application, 2) what are the barriers/obstacles and challenges faced by faculty members when using the social media application for teaching and 3) factors that promote use of social media applications among faculty members [18][33][40] [41]. Previous studies indicated that faculty adoption of social media is still at the early majority adoption level [4]. At this level of adoption, faculty members agreed on the importance and success of adopting the social media application but, they are still cautious on giving their full commitment and efforts in using this application for teaching purposes.…”
Section: Social Media Use For Teaching and Learningmentioning
confidence: 99%
“…The new generation of students whom social media have heavily penetrated their lives has transformed the teaching delivery approaches [4]. HEI integrated the use of social media with their existing learning management system platform to provide students with better learning experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Most of previous researches, centered on the 030003-2 importance of social media to students [14][17][18] [19]. There were studies done previously on academia, however most of it aimed to explore the application of social media for teaching purposes [20] [21]. Therefore, this study will extend the research regarding social media utilization by focusing towards academia perspectives on how they use it for the purposes of knowledge sharing, what are the factors that encourage them to engage in this behavior (i.e.…”
Section: Research Problemmentioning
confidence: 99%